The Effect of Implementing the 8p Digital Marketing Strategy on Purchase Intention for Bvlgari Luxury Perfumes: A Binary Logistic Regression Analysis - Nugraha, Yudi; Threezardi, Ricki; Dwirahmawati, Retno; Heikal, Jerry (CV. Publikasi Indonesia, 2025)
This research examines the influence of the 8P digital marketing mix (Product, Price, Promotion, Place, People, Process, Physical Evidence, Productivity and Quality) on consumer purchase intention for Bvlgari luxury perfumes using binary logistic regression analysis. Data were collected via a Qualtrics survey from 88 respondents in Indonesia. The analysis revealed that among the 8P elements, Price, Public Figures (Promotion/People), and Product Collaboration significantly impacted purchase intention. Price and Public Figures had the strongest positive effects, increasing purchase likelihood by 3.8 and 4.8 times, respectively, aligning with theories of conspicuous consumption and aspirational influence. Conversely, Product Collaboration showed a significant negative effect, reducing purchase intention by 74%, suggesting potential brand dilution risks. Other elements, such as scent preferences and bottle design, were statistically insignificant. The logistic regression model achieved 68.2% overall accuracy, excelling in predicting intent-to-buy (91.7%) but underperforming for non-buyers (17.9%). These findings highlight the importance of premium pricing and influencer partnerships in luxury perfume marketing while cautioning against collaborations that may undermine brand exclusivity. The research provides actionable insights for Bvlgari to refine its digital strategy, emphasizing immersive, trust-driven experiences to offset the limitations of online sensory engagement.